2008
DOI: 10.1097/pec.0b013e31818c2679
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil CD64 Expression as a Diagnostic Marker of Bacterial Infection in Febrile Children Presenting to a Hospital Emergency Department

Abstract: Neutrophil CD64 expression is a sensitive marker for diagnosing bacterial infection in young children, but as it is also raised in viral infection, it lacks specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
0
22
1
Order By: Relevance
“…32,33 Similarly, the PMN CD64 index has been utilized in other disciplines, most notably in the early recognition of neonatal sepsis 34 and other bacterial infections in children. 35 When we compared these two biomarkers in their ability to identify new diagnosis CD, the PMN CD64 demonstrated a superior specificity when a fecal calprotectin cut off of 50 mcg/gm was utilized (90% specificity for PMN CD64 index compared to 29% specificity for fecal calprotectin). While a fecal calprotectin level of >50 mcg/gm has been suggested as the cut point to distinguish IBD from non-IBD, we found that only 4/14 non-IBD controls had a fecal calprotectin <50 mcg/gm.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Similarly, the PMN CD64 index has been utilized in other disciplines, most notably in the early recognition of neonatal sepsis 34 and other bacterial infections in children. 35 When we compared these two biomarkers in their ability to identify new diagnosis CD, the PMN CD64 demonstrated a superior specificity when a fecal calprotectin cut off of 50 mcg/gm was utilized (90% specificity for PMN CD64 index compared to 29% specificity for fecal calprotectin). While a fecal calprotectin level of >50 mcg/gm has been suggested as the cut point to distinguish IBD from non-IBD, we found that only 4/14 non-IBD controls had a fecal calprotectin <50 mcg/gm.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have been used as diagnostic tools in clinical settings: neutrophil absolute count (Wile et al, 2001;Pratt and Attia, 2007;Bressan et al, 2010;Manzano et al, 2011), enumeration of band neutrophils (band count) (Seebach et al, 1997;Al-Gwaiz and Babay, 2007), and the expression levels of neutrophil surface proteins (Nupponen et Rudensky et al, 2008;Dilli et al, 2010;Genel et al, 2012;Jia et al, 2013) to predict bacterial infections and severity outcomes. Due to the increasing evidence of neutrophils being involved in mediating viral diseases (Tumpey et al, 2005;Duffy et al, 2012), it is now possible to develop new diagnostic tools capable of distinguishing between viral and bacterial diseases.…”
Section: Neutrophils As a Tool To Distinguish Between Bacterial And Vmentioning
confidence: 99%
“…They observed increased neutrophil surface CD64 expression in patients with bacterial and viral infections, but significantly more in those with bacterial infection [27]. Despite the very good sensitivity, they did not find that CD64 provided the necessary specificity for diagnosis of bacterial infection at several cutoff values [27]. Among other investigated surface molecules are CD11b, CD32, CD16, CD69, and CD15s [13,28].…”
Section: Discussionmentioning
confidence: 95%
“…One of the investigated leukocyte cell surface molecules is Fcγ receptor I (FcγRI) which is the high affinity receptor for monomeric IgG1 and IgG3, and is recognized by the monoclonal antibody CD64 [5]. Rudensky et al investigated the use of CD64 measurement in young children presenting to the ED with febrile illness [27]. They observed increased neutrophil surface CD64 expression in patients with bacterial and viral infections, but significantly more in those with bacterial infection [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation